Hispanic race is a risk factor for COVID-19 during pregnancy: data from an urban New York City hospital. (4th July 2022) - Elkafrawi, Deena; Sisti, Giovanni; Mercado, Felipe; Rodriguez, Brian; Joseph, Julie; Jones, Chandra; Schiattarella, Antonio; Upadhyay, Ruchi
Abstract: There are limited studies on predisposing factors for COVID-19 positivity in asymptomatic pregnant women. The literature published to date on asymptomatic COVID-19 pregnant carriers does not focus on pregnancy or pre-pregnancy comorbidities. We wanted to identify risk factors for COVID-19 in asymptomatic pregnant women. We performed a retrospective chart review of 263 asymptomatic pregnant women admitted to labour and delivery at New York City Health + Hospitals/Lincoln. We analysed the association between race, body mass index (BMI), smoking, indication for admission, gravidity, parity, pre-pregnancy comorbidity, pregnancy comorbidity via uni- and multivariate statistical tests. Only Hispanic race was significant in the univariate analysis ( p = .049). At the post-hoc analysis, Hispanics had a higher proportion of COVID-19 cases compared to non-Hispanic Blacks ( p = .019). No variables were significantly associated with COVID-19 positivity in the multivariate analysis. Hispanic race appears to be a risk factor for asymptomatic COVID-19 infection during pregnancy. We speculate that the cultural and socioeconomic reality of Hispanic women living in our community leads to more exposure opportunities and therefore, a higher infection rate. Impact statement: What is already known on this subject? Little is known on the role of comorbidities and risk factors that can favour COVID-19 infection during pregnancy. What do the results of this study add? We found that Hispanic pregnant asymptomatic women had a higher rate of COVID-19 in comparison to non-Hispanic Black women. Pre-pregnancy comorbidities such as pregestational diabetes, hypertension and asthma were not associated with COVID-19 positivity. What are the implications of these findings for clinical practice and/or further research? The reasons why the Hispanic race is more affected by COVID-19 during pregnancy is unclear. The social environment of Hispanic women living in our community, such as their tendency to live in multigenerational and multi-family households, might contribute to a higher infection rate. More resources might be dedicated in the future to Hispanic-dense neighbourhoods.